Patch testing with the European baseline series fragrance markers: a 2016 update. (1st March 2018) - Ung, C.Y.; White, J.M.L.; White, I.R.; Banerjee, P.; McFadden, J.P.
Summary: Background: Fragrance contact allergy is common and is currently screened for using the following European baseline series fragrance markers: fragrance mix (FM)I, FMII, Myroxylon pereirae and hydroxyisohexyl 3‐cyclohexene carboxaldehyde. Objectives: To investigate the validity of patch testing using these fragrance markers in detecting fragrance allergy to 26 individual fragrance substances for which cosmetic ingredient labelling is mandatory within the European Union. Methods: We conducted a retrospective review of the patch test records of all patients with eczema who underwent testing using the European baseline series, extended with the individual fragrance substances during the period from 2015 to 2016. Results: Overall, 359 patients (17·2%) reacted to one or more allergens from the labelled fragrance substance series and/or a fragrance marker from the European baseline series. The allergens that were positive with the greatest frequencies were oxidized linalool [ n = 154; 7·4%, 95% confidence interval (CI) 6·3–8·6], oxidized limonene ( n = 89; 4·3%, 95% CI 3·4–5·2) and Evernia furfuracea ( n = 44; 2·1%, 95% CI 1·5–2·8). Of the 319 patients who reacted to any of the labelled fragrance substances, only 130 (40·8%) also reacted to a baseline series fragrance marker. The sensitivity of our history‐taking for detecting fragrance allergy was 25·7%. Conclusions: Given the evolving trends in fragrance allergy, patch testing with FMI, FMII, M. pereirae and hydroxyisohexyl 3‐cyclohexene carboxaldehyde is no longer sufficient for screening for fragrance allergy.